Development of Hots-Based E-Modules Using Integration of Digital Technology in Arabic Language Learning - Susanti, Susanti; Baroroh, R. Umi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to produce an Arabic language learning E-Module based on Higher Order Thinking Skills (HOTS) using digital technology integration, to determine the results of validation by subject matter experts, media experts, and education practitioners, as well as the strengths and weaknesses of the E-Module developed for Arabic language learning. This study is a Research & Development (R&D) using the 4D development model (Define, Design, Develop, Disseminate). Data was collected through observation, interviews, questionnaires, and document studies in eighth grade at SMP Islam Al Azhar 46 Pati to determine the suitability of the material and media contained in the E-Module with the student needs. Data analysis techniques in this study used a Likert scale to measure the validity and feasibility of the E-Module. The results of the validation by subject matter experts, media experts, and education practitioners on the developed E-Module were categorized as very good with a percentage of 92.80%. The advantages of HOTS-based E-Modules using digital technology integration that have been developed in Arabic language learning include ease of access through various devices anywhere and anytime as long as there is an internet connection; fostering discipline, critical thinking skills, creativity, teamwork, and self-confidence; and more interactive presentation of E-Modules. However, there are also some limitations, such as the need for a significant amount of time in developing the E-Module; the absence of a direct two-way discussion space within the E-Module; and the requirement for teachers to act as facilitators, continuously monitoring the learning process, providing support, and motivating students.